Global climate change attitudes and perceptions among south American zoo visitors. Issue 4 (28th May 2015) - Luebke, Jerry F.; Clayton, Susan; Kelly, Lisa‐Anne DeGregoria; Grajal, Alejandro
<x xml:space="preserve">Abstract</x> There is a substantial gap between the scientific evidence for anthropogenic climate change and the human response to this evidence. Perceptions of and responses to climate change can differ among regions of the world, as well as within countries. Therefore, information about the public's attitudes and perceptions related to climate change is essential to the development of relevant educational resources. In the present study, zoo visitors in four South American countries responded to a questionnaire regarding their attitudes and perceptions toward global climate change. Results indicated that most respondents are already highly concerned about global climate change and are interested in greater engagement in pro‐environmental behaviors. Visitors also perceive various obstacles to engagement in climate change mitigation behaviors. We discuss the results of our study in terms of addressing visitors' climate change attitudes and perceptions within the social and emotional context of zoo settings. Zoo Biol. 34:393–393, 2015. © 2015 Wiley Periodicals Inc.